Development of an extended STIRPAT model to assess the driving factors of household carbon dioxide emissions in China. (1st January 2023) - Yu, Shiwang; Zhang, Qi; Hao, Jian Li; Ma, Wenting; Sun, Yao; Wang, Xuechao; Song, Yu
Abstract: Although the past twenty years have witnessed China's remarkable economic development, the cost in terms of greenhouse gas emissions and a deteriorating environment has been enormous. Numerous studies have revealed the influence of household factors on household carbon dioxide emissions (HCEs) and called for a reduction of HCEs to mitigate climate change, but few have focused on assessing the most significant household driving factors of HCEs. Using statistical data between 2005 and 2019 in Jiangsu, China, this study developed an extended stochastic impact by regression on population, affluence, and technology (STIRPAT) model to assess the most significant driving factors of HCEs. The results show that the most significant driving factors are household size, total population, unemployment, and urbanisation rate. The study found that HCEs are positively impacted by household size while negatively impacted by the unemployment rate. Based on the study's findings, the following suggestions are proposed to lower HCEs: (i) establish an optimal consumption concept to guide residents towards consuming reasonably; (ii) cultivate a low-carbon concept among residents and promote low-carbon emissions living; and (iii) pay close attention to population structure factors and formulate effective measures accordingly. The study provides insightful information on the key driving factors of HCEs, which can facilitate achieving carbon emissions neutrality. Highlights: H1: The driving factors of household CO2 emissions (HCEs) are identified. H2: An extended STIRPAT model is developed for assessing the driving factors. H3: The household factors are ranked resulted from the ridge regression analysis. H4: The household size is the most significant positive factor of HCEs. H5: Unemployment has a negative impact on HCEs.